If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 7 = 67 Reorder the terms: 7 + 12x = 67 Solving 7 + 12x = 67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 12x = 67 + -7 Combine like terms: 7 + -7 = 0 0 + 12x = 67 + -7 12x = 67 + -7 Combine like terms: 67 + -7 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| 10*120= | | -2=-8-5x | | 3x^2-4a-7=0 | | 8a^2b^2-2ab= | | -6+4(x-2)=13x+5-9x | | X^2+16x+65=0 | | .0002x^2-.316x+127.9=5 | | 9(7x+5)=6(10x+8) | | 10x^3-4x^2+15x-6=0 | | 7x+6x-2x=16+x+5x+9 | | 3P-1=59(P-1)-2(72P) | | 40X^3+50X^2=0 | | -5(t^2+2t+10)=0 | | 14x-5-5x=9-x+6 | | -29-5x=4x+20 | | 4x^2-27x+17=-7x+8 | | -x+15=f(15) | | 8x+5+12-6x=30 | | 2x+183=9x+6 | | 9-(2x-4)=-2+3x | | -0.08769x^2+1.7269x+2=0 | | 3(x-8)=4 | | 5(2x-3)=10 | | 3(3x+1)=12 | | x^2+4x+8=-2x+3 | | g(x)=3x+9 | | 4x+20=2.5x+35 | | -5t^2+10t+50=0 | | (w+9)(w-9)= | | 49x^2-4= | | 5t^2+10t+50=0 | | 24x^2-96x+116=0 |